The influence of demographics on continuous improvement strategic planning - Brenes-Bastos, Melissa (2017)
The process of innovate by creating or modifying a product, and how it is introduced into the market is difficult to implement due to the perceptions of the staff involved. The continuous improvement process helps to make innovation sustainable. Current research aims to describe the relationship between demographics and the continuous improvement process. The work done will serve as a reference for industries implementing or planning to implement continuous improvement, and to academia as well. The results shown were collected by application of a self-administered survey to 150 works from 5 different companies. Resulting data demonstrated that some demographic characteristics have an effect on how workers perceive the continuous improvement process inside organizations. The main limitation of the study is that the methodology of case study selected makes conclusions only on the participating cases. Thus, more research to validate data in other companies will be required.